From contractors to investors? Evolving engagement of Chinese state capital in global infrastructure development and the case of Lekki Port in Nigeria - Hong Zhang (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2023)
This paper introduces and critically analyzes an emerging form of global infrastructure development by China's infrastructure construction companies, known as "integrated investment, construction, and operation" (IICO). This model has been promoted by the Chinese infrastructure industry, financial institutions, and policymakers in recent years, as a response to the moral hazard problems exposed in the past sovereign loan-based infrastructure engagements, the industry's need to upgrade, and the global rise of PublicPrivate Partnerships. IICO can be understood as a form of market-seeking foreign direct investment. Compared to past forms of globalization of Chinese state capital, it has a much more complicated risk profile and less clear pay-off. While Chinese state capital actors are not yet well equipped to manage such new risks, they have been driven to make such attempts by the political pressure to become globally leading firms. A case study of Lekki Port in Nigeria serves to illustrate the challenges in the transition toward IICO. This paper calls for continued attention to this emerging form of Chinese state capital's engagement in global infrastructure development, especially on how risks are managed and the implications for the relationships between Chinese actors and host country stakeholders.
Keywords: 330; Infrastrukturinvestition; Auslandsinvestition; Öffentlich-private Partnerschaft; Öffentliches Unternehmen; Bauwirtschaft; Hafen; China; Nigeria; Afrika